The Conservative and Dynamic Nature of Indigenous Knowledge: A Case Study from Kenya - Randall D. Beckloff (Adult Education Research Conference, 2008)
Abstract: Indigenous knowledge in Africa conserves traditional community heritage and is dynamically adjusted as communities adapt to contemporary realities. This roundtable considers these conservative and dynamic natures as portrayed in a case study from Kenya and poses discussion questions.
Keywords: indigenous knowledge; local knowledge; Africa; Kenya; Giriama